Conservation Subdivision: Construction Phase – Dark-sky Lighting - Mark Hostetler (EDIS)
WEC283, a 4-page illustrated fact sheet by Mark Hostetler, discusses how to manage lighting during the construction phase and explains the importance of good lighting to biodiversity in a conservation subdivision. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, April 2010.